Stent strategies in left main bifurcation lesions: the simpler, the better?. (14th October 2021) - Oliveira Campos, G; Leite, L; Santos, M; Paiva, L; Jorge, E; Silva, J; Matos, V; Oliveira, H; Costa, M; Goncalves, L
Abstract: Introduction: Although percutaneous coronary intervention (PCI) for ostial or midshaft lesions in left main (LM) disease has shown similar results as compared with coronary artery bypass grafting (CABG), distal LM bifurcations are associated with an increase in procedural complexity and higher rates of target lesion revascularization. Several studies have investigated the optimal stenting strategy in patients with coronary bifurcation lesions and showed no benefit for systematic two-stent approach in comparison with provisional stenting. This is reflected in the current guidelines that recommend provisional stenting of the side branch as the preferred approach for most bifurcation lesions. However, there is still debate about the optimal strategy according to lesion location. Objectives: This analysis aimed to compare the clinical outcomes of LM bifurcation PCI using a provisional strategy versus a two-stent strategy. Methods: Retrospective, observational study including patients submitted to LM bifurcation (Medina 1, 1, 1) PCI between January 2010 and December 2019. Data was collected from the emergency department and hospitalization registries. Patients were divided according to the stenting approach. We made a global analysis including baseline clinical and angiographic data. The primary endpoint was target lesion failure (TLF), defined as the composite of myocardial infarction, cardiac death, and target lesion revascularization (TLR). Secondary endpoints included the individual components. Results: A total of 106 patients were included (median age 74 [66–82], 79 (74.5%) males), 57 (53.8%) submitted to provisional stenting and 49 (46.2%) to a two-stent technique. Baseline characteristics were well matched (table 1). The mean SYNTAX score was 29.6±10.0 and LM stenosis grade was ≥70% in all lesions. Median follow-up was 26.6 [12.0–48.6] months. No differences were found regarding the primary endpoint (TLF in provisional stenting was 21.7% vs 21.4%, HR 2.432; 95% confidence interval, 0.472–12.450; p=0.233.). Although target lesion revascularization within the LM complex was numerically higher in the two-stent group (10.2% vs. 3.5%, p=0.245), the opposite was found in cardiac death (provisional group 10.5% vs. 4.3%, p=0.289). Conclusions: Besides being a "simpler" technique, provisional stenting had no significant differences in outcomes compared to two-stent techniques. Without further evidence, revascularization strategies should primarily rely on operator expertise. Funding Acknowledgement: Type of funding sources: None.